Adenocarsinoma Paru Kanan Stadium Lanjut yang Menyebabkan Hidropneumothorax pada Perempuan yang Bukan Perokok - Rosmiati Rosmiati; Indra Buana (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Lung adenocarcinoma is one of the most common types of lung cancer, especially in non-smoking women. This disease can develop progressively to cause complications such as pleural effusion and hydropneumothorax. Risk factors involved include exposure to secondhand smoke, air pollution, radon, and a history of previous tuberculosis. A 61-year-old woman came with complaints of right chest pain radiating to the back, shortness of breath, dry cough, weakness, and weight loss. The medical history showed that the patient had undergone chemotherapy for lung cancer and had a history of pulmonary tuberculosis that had been resolved. Supporting examinations such as CT-scan, bronchoscopy, and cytology showed a mass in the right lung inferior lobe and massive pleural effusion leading to a diagnosis of stage IVA right lung adenocarcinoma (T3N1M1A) complicated by hydropneumothorax. The patient underwent management in the form of chemotherapy, supportive therapy, and symptomatic care.